2019
DOI: 10.1136/sextrans-2018-053892
|View full text |Cite
|
Sign up to set email alerts
|

Changes in risky sexual behaviours among West African MSM enrolled in a quarterly HIV testing and counselling prevention programme (CohMSM ANRS 12324 – Expertise France)

Abstract: ObjectivesWhether regular HIV testing and counselling reduce risky sexual behaviours in African men who have sex with men (MSM) is still a matter for debate. We aimed to identify behavioural trajectories based on HIV risk exposure (HRE) and factors affecting their evolution.MethodsData were collected from 621 HIV-negative West African MSM (Mali, Cote d'Ivoire, Burkina Faso and Togo) included in a community-based cohort providing quarterly HIV testing and counselling. Sociobehavioural data were collected every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Several studies demonstrated that poorer mental health (especially severe depression, depression and PTSD, or anxiety) was associated with less consistent condom use or less perceived condom self-efficacy among MSM [80], young women who sold sex [81], and homeless men who also used drugs and traded sex [82]. Condom use self-efficacy and depression were partial mediators of the relationship between sexual stigma and inconsistent condom use among MSM [83].…”
Section: The Relationship Of Mental Health To Hiv Prevention Behavioursmentioning
confidence: 99%
“…Several studies demonstrated that poorer mental health (especially severe depression, depression and PTSD, or anxiety) was associated with less consistent condom use or less perceived condom self-efficacy among MSM [80], young women who sold sex [81], and homeless men who also used drugs and traded sex [82]. Condom use self-efficacy and depression were partial mediators of the relationship between sexual stigma and inconsistent condom use among MSM [83].…”
Section: The Relationship Of Mental Health To Hiv Prevention Behavioursmentioning
confidence: 99%
“…4 A significant increase in condom use among MSM following preventive education has recently been reported in a cohort of MSM in west Africa. 23 We found that condom use with paying partners (commercial sex) was associated with a 60% lower likelihood of HIV infection in this study. This increase in protected commercial sex may partly explain the decreased HIV prevalence observed in this study.…”
Section: Discussionmentioning
confidence: 46%
“…In a previous analysis, we found that MSM at greater risk of exposure to HIV infection decreased their risky sexual behaviours during their follow-up in CohMSM, suggesting a potential positive effect of the quarterly prevention services on those who need it most [25]. However, the high HIV incidence and the lack of association between adherence to these services and incident HIV infections observed in the present analysis strongly suggest that this intervention alone is insu cient to signi cantly reduce the burden of the epidemic in this population.…”
Section: Discussionmentioning
confidence: 78%